2021
DOI: 10.1039/d1dt02219a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical control of [FeFe]-hydrogenase single crystals reveals complex redox populations at the catalytic site

Abstract: Elucidating the distribution of intermediates at the active site of redox metalloenzymes is vital to understanding their highly efficient catalysis. Here we demonstrate that it is possible to generate, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
0
13
0
3
Order By: Relevance
“…The method reported here, already extended to crystals of C. pasteurianum [FeFe] hydrogenase I, 78 is likely to have general relevance in structure–function studies of complex redox metalloenzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method reported here, already extended to crystals of C. pasteurianum [FeFe] hydrogenase I, 78 is likely to have general relevance in structure–function studies of complex redox metalloenzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, we now show that, within single crystals of Hyd1, it is possible to achieve control over the full manifold of states observed in solution for this enzyme. A related report by Morra et al demonstrates electrochemical manipulation of [FeFe] hydrogenase I from Clostridium pasteurianum using similar methods, 78 and these studies present the possibility for using electrochemical control over single protein crystals to establish samples in the solid state for further structural study.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, H inact could be reached by (electro)­chemical oxidation in the absence of O 2 . Recently, the Vincent group demonstrated that this approach could be extended to study individual crystals of [FeFe]-hydrogenase from Clostridium pasteurianum (“CpI”), using a cocktail of electron mediators to shuttle electrons and ultimately control the redox state of the enzyme during FTIR microspectroscopy . Importantly, this approach allowed all of the catalytically relevant states of CpI to be probed, in addition to identifying a previously undetected catalytic state ( H redH + ).…”
Section: Methods To Study Enzymatic and Microbial Electrodesmentioning
confidence: 99%
“…Additionally, RR and IR spectroscopic studies were successfully performed on the same single hydrogenase crystals, complementing the crystallographic data and facilitating structural assignment of ambiguous inhibited and active redox states, such as the oxygen-stable H inact and the hydrogen-binding intermediate Ni a -S state in [FeFe] and [NiFe] hydrogenases, respectively [86,89]. Notably, well-defined redox states in hydrogenase single crystals for IR imaging have been generated by electrochemical and gas control [90][91][92][93]. Furthermore, Fe-OH ligation at the unprecedented [4Fe-3S] cluster of the O 2 -tolerant membrane-bound [NiFe] hydrogenase from R. eutropha has been identified by RR spectroscopy and confirmed by theoretical quantum and molecular mechanics methods [94,95].…”
Section: Hydrogenasesmentioning
confidence: 99%